Do sangue à tinta: a escrita de si como mediação para a autonomia de estudantes que se autolesionam - Madeira, Luis Claudio Nogueira (2020)
Non-suicidal self-harm is a reality that is increasingly present in the daily life of schools, not only in Brazil but in different continents. According to studies, the estimated prevalence is that 8.9% of female adolescents between 15 and 16 years old present non-suicidal self-harm, as this shows that the problem affects a vulnerable and important part of the population and that the efforts of the international scientific community , as well as child and adolescent protection and development agencies, demand production of knowledge about the phenomenon. In this study, self-injury in adolescence is read as having its genesis in the difficulty of symbolizing in the face of adverse situations, since these young women did not have the opportunity to develop autonomy in the face of a psychosocial reality of subjection. The objective of the research was to analyze the mediation of self-writing processes in the construction of the autonomy of self-insulting students. For the development of the research, the Ateliê de Escrita de Si was held, a school formative process permeated with literacy practices in self-writing organized from a series of 13 semi-structured sessions. In it, the adolescents elaborated 57 productions among writings, drawings and comics that were analyzed through the Discursive Textual Analysis. The Ateliê enabled the widening and deepening of the participants' autonomy as they strengthened their self-knowledge, their selfacceptance and the reframing of their experiences. The data also revealed aspects of the subjectivity of young women in their relationship with themselves, with their respective families and friends, in gender relations, at school and in the appropriation of underground / gothic cultural elements. The students expressed meanings in their self-harm practices due to guilt and stigmatization, in order to obtain relief and escape from uncomfortable emotional states, as well as, related to loneliness and difficulty in socializing. Finally, the potential of self-writing for the researcher's access to psychic, educational and social senses and processes in mediation with self-insulting adolescents was evidenced.